From Lazarillo to ‘Otro Lazarillo’: the picaresque novel in Golden Age Spain - Folger, Robert (The Routledge Hispanic studies companion to early modern Spanish literature and culture, 2022)
Based on an overview of scholarship and the most important texts of the genre, this chapter situates the Spanish picaresque novel in relation to the fabric of Golden Age society and culture, emphasizing the rogue’s desire for social ascent and recognition. The first picaresque novel, Lazarillo de Torres (1554), can be described as a service record that the protagonist writes concerning the instigation of the Subject of power. It is an instance of ideological interpellation: the protagonist accepts the social order and is, simultaneously, empowered, ensuring his modest ascent in society. While the narrative formula and the ideologeme established in Lazarillo is the rationale of later picaresque novels, the emancipatory impulse of the urtext is subsequently quelled. In the final Golden Age picaresque novel, Estebanillo González (1646), the kernel of interpellation so typical of the genre once again takes center stage. The author resolves the inconsistency between the ‘I’ of enunciation and the ‘I’ of the narration, yet succumbs to elite ideology, discrediting social mobility for good.
Gesehen am 21.01.2024